The Flexible Initiation Test (FIT): A new experimental test to characterize fracture initiation in mode I at the free edge of bonded assemblies. (August 2018) - Bui, Q.; Maurel-Pantel, A.; Mazerolle, F.; Hochard, C.
Abstract: Direct bonding is based on molecular adhesion. This bonding technique consists to join two surfaces into direct contact without the use of any adhesives or additional material. This process requires clean surfaces with a nanometric roughness, sufficiently close together to initiate bonding. Mechanical characterization of this type of assembly with classical mechanical test as for instance wedge test, cleavage test or double shear test present a highly scattering on mechanical results. This paper presents the Flexible Initiation Test (FIT test), an original test designed to characterize fracture initiation in mode I, and to decrease scattering in fracture initiation load measurements, in particular for adhesive with brittle behavior. This new test has to take into account the industrial framework: to be easy to manufacture, easy to execute repeatedly and efficient to provide experimental data for numerical models (stress criteria applications for instance). The paper proceeds first with an explanation of the main initial ideas to introduce the concept of this new test. Next, a numerical analysis is proposed to validate the concept and to determine the optimal geometry of the tests. Then the experimental device is set up and the concept is validated on three different adhesives with the same substrate (a brittle cyanoacrylate adhesive, a ductile and a brittle epoxy adhesives). To conclude, the FIT test is applied on direct bonded samples (an extreme case nanometric interface and very brittle behavior) to determine the fracture initiation load and to compare scattering of measurements.